AN ANALYSIS OF THEME AND RHEME USED IN THE FIVE-STAR HOTELS’ WEB SITES IN SURABAYA - Gabriel Stella; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
The study done by the writer observes the themes and rhemes used in the five-star hotels’ web sites in Surabaya. It includes the types of themes and the notions of subject which are under the Systemic Functional Grammar (SFG) proposed by Halliday and Matthiessen (2004). In addition, the data of the study are in the form of text and taken from seven Surabaya five-star hotels’ web sites. The writer also used a descriptive qualitative approach in analyzing the 155 data. From the analysis, it is found the two kinds of structure of theme and rheme used by the hotels in their web sites. The hotels also used three types of theme which are simple theme, clause as a theme, and thematic equative. In terms of the subjects (psychological subject, grammatical subject, and logical subject), the hotels are able to fulfill either one, two, or three notions of subject.